Optimizing the Creative Batik Industry in Situbondo and PKK Groups Through Innovation in Automatic Batik Pattern Machines and Food Dehydrator Machines in the Extremely Poor Area of Selowogo Village - Suyanto; Liosten Rianna Roosida Ully Tampubolon; Fadjar Kurnia Hartati; Muhammad Hayyu Hani Nuril; M. Afrizal Adi Pratama; Andini Safitri; Hawari Abariyah Marasabessy (Unram Journal of Community Service, 2025)
This service activity aims to optimize the potential of the batik creative industry in Selowogo Village, Situbondo, and to empower the PKK Group through appropriate technology innovations in the form of an automatic batik pattern machine and a food dehydrator machine. This program focuses on extremely poor areas with an average income of below Rp50,000 per day. The activity approach includes socialization, training, technology implementation, mentoring, and sustainability evaluation. The results of the activities show significant improvements, including a 30% increase in batik production capacity, a 40% improvement in motif quality, and a 35% increase in sales revenue. For the PKK Group, skills in making batik and healthy food products based on moringa leaves increased by 50% and 70%, respectively. This program successfully promoted local economic empowerment, strengthened creative industry innovation, and contributed to achieving SDGs 1 (no poverty) and 3 (good health and well-being).